2020
DOI: 10.1002/ajmg.a.61544
|View full text |Cite
|
Sign up to set email alerts
|

GARS‐related disease in infantile spinal muscular atrophy: Implications for diagnosis and treatment

Abstract: The majority of patients with spinal muscular atrophy (SMA) identified to date harbor a biallelic exonic deletion of SMN1. However, there have been reports of SMA-like disorders that are independent of SMN1, including those due to pathogenic variants in the glycyl-tRNA synthetase gene (GARS1). We report three unrelated patients with de novo variants in GARS1 that are associated with infantile-onset SMA (iSMA).Patients were ascertained during inpatient hospital evaluations for complications of neuropathy. Evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…In 2012, Eskuri et al reported monozygotic twin girls from the United State with a severe, infantileonset CMT2D/dSMA-V (Eskuri et al, 2012), similar to the patient reported by James et al (2006), and a mutation (G652A) within the anticodon-binding domain of GARS1 was found by direct Sanger sequencing (Eskuri et al, 2012). Afterward, eight individuals with infantile-onset CMT/ dSMA-V were reported from Taiwan, Korea, and the USA, and the genetic tests were performed by next-generation sequencing (NGS), including panel, ES, or trio-ES (Chae et al, 2015;Chung et al, 2018;Eskuri et al, 2012;James et al, 2006;Liao et al, 2015;Markovitz et al, 2020). All these mutations identified in these patients were de novo, except three siblings from a Nigerian descent family in the USA, whose variant (c.815T>G, p.L272R) was inherited from their healthy mother with low-level (10%-20%) mosaicism (Chung et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In 2012, Eskuri et al reported monozygotic twin girls from the United State with a severe, infantileonset CMT2D/dSMA-V (Eskuri et al, 2012), similar to the patient reported by James et al (2006), and a mutation (G652A) within the anticodon-binding domain of GARS1 was found by direct Sanger sequencing (Eskuri et al, 2012). Afterward, eight individuals with infantile-onset CMT/ dSMA-V were reported from Taiwan, Korea, and the USA, and the genetic tests were performed by next-generation sequencing (NGS), including panel, ES, or trio-ES (Chae et al, 2015;Chung et al, 2018;Eskuri et al, 2012;James et al, 2006;Liao et al, 2015;Markovitz et al, 2020). All these mutations identified in these patients were de novo, except three siblings from a Nigerian descent family in the USA, whose variant (c.815T>G, p.L272R) was inherited from their healthy mother with low-level (10%-20%) mosaicism (Chung et al, 2018).…”
Section: Discussionmentioning
confidence: 53%
“…To date, a total of 12 patients have been reported to present clinical symptoms of CMT2D/dSMA-V at infancy or early childhood, caused by seven missense mutations, c.598G>T (p.D200Y), c.815T>G (p.L272R), c.998A>G (p.E333G), c.1001T>A (p.L334N), c.2313G>C (p.G598A), c.1954G>C (p.G652R), and c.1955G>C (p.G652A), respectively (Chae et al, 2015;Chung et al, 2018;Eskuri et al, 2012;James et al, 2006;Liao et al, 2015;Markovitz et al, 2020). As shown in Table 1 and Figure 1f, among these variants, only the variant (p.L272R) lies on catalytic domain, three mutations, p.G652R, p.G652A, and p.G598A on anticodon-binding domains, and the other three (p.D200Y, p.E333G, and p.L334N) on dimer interface regions (Figure 1f).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case of aminoacyl-tRNA transferases. Mutations in the gene methionyl-tRNA synthetase ( MARS1 ) identified in Charcot-Marie-Tooth disorder type 2U (CMT2U); in glycyl-tRNA synthetase 1 ( GARS1 ) associated with CMT (CMT2D) and with Spinal muscular atrophy; and infantile, James type (SMAJI), and valyl-tRNA synthetase ( VARS1 ), associated with developmental encephalopathy with microcephaly have been successfully studied in yeast [ 46 , 47 , 48 ]. In these studies, gene variants are not retrieved from databases but identified in patients and their families because they are so rare that they have been never reported elsewhere.…”
Section: The Study Of Genetic Variation Of Single Genesmentioning
confidence: 99%
“…Moreover, it is known that a form of GARS , in which both MTS and WHEP-TRS domains are truncated (MTSΔWHEPΔ), is able to complement the lethality due to the deletion of GRS1 [ 80 , 81 ]. This heterologous complementation approach allowed to demonstrate that I334N and G327R GARS variants do not support the growth of yeast, indicating a severe impairment of protein function [ 26 , 27 ].…”
Section: Functional Studies Of Mt Ars Genes Mutations In Yeastmentioning
confidence: 99%